Pengaruh Model Pembelajaran Student Team Achievement Division dan Teams Games Tournament Terhadap Hasil Belajar IPA Materi Sistem Pencernaan Manusia Kelas VIII di MTS Kecamatan Sarang Kabupaten Rembang - Siti Chotijah; Rismiyanto Rismiyanto; Ahmad Hilal Madjdi (Peneliti.net, 2022)
The aims of the study were to 1) determine the effect of the Student Team Achievement Divisions (STAD) learning model on the science learning outcomes of the Human Digestive System material on students. 2) determine the effect of the Teams Games Tournament (TGT) learning model on the science learning outcomes of the Human Digestive System material on students. 3) to find out the differences between the Student Team Achievement Divisions (STAD) and Teams Games Tournament (TGT) learning models on the science learning outcomes of the Human Digestive System material for students. This study uses an experimental approach with a pure experimental type because of the experimental and control classes, while the design used is the pretest posttest control group design. Research results: 1) The Student Team Achievement Division (STAD) model has an effect on learning outcomes in science learning material for the human digestive system class VIII at MTs Sarang Rembang, this is based on the acquisition of a Tcount value of 13,291 > t-table 2,06390 and a significance level of 0.000 < 0, 05. 2) The Teams Games Tournament (TGT) learning model has an effect on the science learning outcomes of the VIII grade human digestive system material at MTs Sarang Rembang, this is based on the acquisition of a Tcount value of 25,485 > t-table 2,06390 and a significance level of 0.000 <0.05. 3) The TGT learning model is more effective than STAD on the science learning outcomes of class VIII human digestive system material at MTs Sarang Rembang, this is based on the Tcount value of 2.278 > Ttable 2.01063 and the significance level of 0.005 <0.05 and the mean value obtained TGT is higher than the mean value in STAD learning (86.4 > 78.66).